KNOWLEDGE MANAGEMENT SYSTEM TROUBLESHOOTING KOMPUTER MENGGUNAKAN SECI MODEL: STUDI KASUS DIVISI IT DEZA COMPUTER - ARI IRAWAN (Faktor Exacta, 2016)
Knowledge Management System (KMS) foster the company into a learning organization. However, this knowledge should be managed, planned and implemented. So expect the existing knowledge within the company is not dependent on humans (employees). In this case, is in need an alternative in handling troubleshooting. With the web-based technology management system, the role of knowledge can be felt. In this study will build a Knowledge Management System with SECI model approach based website that will be applied to Deza Computer. Applications built will be two stages of testing, blackbox testing and test functionality with the quality of the system (SQA) with the aim to measure the quality of software based on the factors and criteria established. After testing, the total value of the quality of the software is 706.35% with a fairly well.Keywords: Knowledge Management System, SECI Model, functionality, blackbox, SQA.